Cultural Connections: An Ethnocultural Counseling Intervention for Black Women in College. Issue 1 (6th April 2018) - Jones, Martinque K.; Sam, Thomandra S
Abstract : Counseling interventions that support the exploration of ethnocultural concerns are beneficial to the overall well‐being of Black women in college. The authors describe Cultural Connections, a theoretically based and culturally adapted group counseling intervention for Black women in college. Also presented are a case example demonstrating the intervention's utility and recommendations for implementation in college counseling centers.